Social influence, financial benefit, and e-wallet multi-brand loyalty: The mediating impact of commitment - Widyoretno Adiani; Atik Aprianingsih; Ira Fachira; Teresia Debby; Andhiny Puspa Maharatie (Cogent Business & Management, 2024)
E-wallet services have become a preferred option for digital payments and are expected to continue growing globally over the next few years. A recent trend suggests Millennial consumers use multiple e-wallet services, leading to questions about the concept of loyalty, particularly in the electronic financial services sector. This study aims to investigate whether multi-brand e-wallet users have loyalty and the variables that build loyalty toward the providers they use. The study uses an online survey based on the stimulus-organism-response theory with four independent variables: network externalities, financial benefits, social pressures, and brand advocacy. Purposive sampling was used to collect data from the Millennial Generation through online questionnaires that were distributed through social media and mailing lists, resulting in a sample of 467 respondents. Partial Least Squares Structural Equation Modeling was used to reveal how these variables have positive relationships with users' commitment, which leads to multi-brand loyalty behavior. This study contributes to the literature by enhancing the study of loyalty issues, especially in e-wallet services.
Keywords: 650; commitment; e-wallet; financial benefit; multi-brand loyalty; social influence